Atraumatic Restorative Treatment and Interim Therapeutic Restoration: A Review of the Literature - Afnan M. Saber; Azza A. El-Housseiny; Najlaa M. Alamoudi (MDPI AG, 2019)
This review discusses the techniques and uses of atraumatic restorative treatment (ART) and interim therapeutic restoration (ITR) and states the differences between these two approaches. ART and ITR are similar approaches and are performed using the same material, but they differ in the purpose of their use. ART is used in cases when there are obstacles to reaching dental care units and has been proven to have high success rates in primary and permanent dentitions. ITR is used as a temporary restoration that will be replaced with a more definitive one. ITR is used in cases when the ideal dental treatment cannot be performed. Conventional glass polyalkenoate (ionomer) restorative cement (GIC) is the material of choice that has been used for ART and ITR. This is because of its fluoride release properties, including its ability to bond to enamel and dentine, its pulpal biocompatibility, and its ease of manipulation. High-viscosity glass ionomer performed better than low and medium-viscosity glass ionomer in ART. Combining GIC with conditioner, as well as the use of a chemo-mechanical approach, improved the success rate of ART. Both ATR and ITR are acceptable strategies, with success rates comparable to the traditional treatment methods.